Phase Separation and Domain Formation in Multi-Component Membranes: Finsler Geometry Modeling and Monte Carlo Simulations - Usui Satoshi; Koibuchi Hiroshi (MATEC Web of Conferences, 2016)
In this paper, we study a surface model for membranes of three components such as DPPC, DOPC, and Cholesterol. This membrane is experimentally well known to undergo the phase separation and to form the domain structure such as the liquid ordered (Lo) phase and the liquid disordered phase (Ld). It is also well known that this multicomponent membrane has a lot of domain pattern transitions between the circular domains and the striped domain etc. Using the new surface model constructed on the basis of Finsler geometry, we study why those morphological changes appear on the spherical vesicles. In our model, we introduce a new variable σ (∈Z2 to represent the domains Lo and Ld , and using the value of σ we define a metric function on the surface. As a consequence, the origin of the line tension energy, which has been used to explain the domain pattern transition in the multicomponent membranes, is naturally understood in our model.